Perbandingan efektivitas penggunaan audio visual terhadap penurunan kecemasan anak selama perawatan gigi di TK Pertiwi dan TK Raudhatul Jannah Banda Aceh - M. Erfin Febrian; Aulina Adami; Asnawi Abdullah (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Anxiety in children about dental care is a problem that arises in children. This is because the dentist's perception and introduction to children does not start early.Objectives: This study aims to compare the effectiveness of the use of audio visuals on reducing children's anxiety during dental treatment at Pertiwi and Raudhatul Jannah Kindergarten in Banda Aceh.Methods: This study uses a cross-sectional study design which is a study conducted to find the relationship between the independent variables (risk factors) and the dependent variable anxiety in dental care. Sampling was done by purposive sampling with the criteria of children aged 5-6 old. The number of samples is 100 samples. Test analysis using the dependent t-test and was analyzed using the stata 14.Results: The results showed, the comparison between the first day and the second day showed a difference in the decrease in anxiety level with the child's anxiety score with intervention of 2.78 with a deviation of 1.379 while the second group without intervention had a decrease in the mean score of anxiety, which was 2.48 with a deviation of 1.455. The difference in the decrease in anxiety scores in children is 0.30. The results of the T-Dependent statistical test obtained a value of p= 0.001Conclusion: In other words, the results of this study can show differences in the level of anxiety in the intervention group with the group that did not use the audio visual intervention.